123 Irish patients' perceptions of their risk for a heart attack in the future following the diagnosis of acute coronary syndrome. (16th May 2012) - O'Brien, F; Mooney, M; O'Donnell, S; McKee, G; Moser, D
Abstract : Introduction: People who perceive themselves to be at risk of an acute coronary syndrome (ACS) are more likely to seek treatment when ACS symptoms arise. This in turn leads to appropriate treatment-seeking behaviour and earlier medical intervention, which are crucial to successful outcomes. However, many people fail to appreciate their true risk of a future heart attack and are thus less likely to seek timely treatment for ACS symptoms. Consequently, their risk of mortality and morbidity is increased relative to those who perceive themselves to be at risk. The aims of this study are to ascertain how individuals who have been diagnosed with ACS perceive their future risk of heart attack and to identify the differentiating characteristics associated with perceptions of such risk. Methods: Data were collected from 1946 patients admitted to hospital with an ACS event. Recruitment took place across five of the major acute hospitals in Dublin, Ireland. Ethical approval was granted for this cross-sectional study. The ACS Response Index was the research instrument used for this study. As a component of this, patients were asked the following question: "Compared to other people your age, how likely do you think it is that you could have a heart attack in the next 5 years?" Data were analysed using PASW v18. Results: The total sample mean age was 63 years±11.7 years, 72% were male. Patient diagnoses comprised of: STEMI (28%), NSTEMI (36.4%) and unstable angina (35.6%). A total of 732 (37.6%) felt that their risk was about the same as others their age, while 359 (18.5%) felt that their risk was lower. The remaining 855 (43.9%) felt their risk was higher than others their age. To determine the characteristics of those who accurately assessed their risk (felt that relative to others their own age, it was at least equivalent or higher) we performed logistic regression using the following variables: age, gender, education level, history of angina, history of myocardial infarction, history of angioplasty, previous coronary artery bypass surgery, diabetes, current smoking status, hypercholesterolaemia and hypertension. Those who perceived themselves to be at higher risk of a future event were more likely to be female (p<0.001), have a higher education level (p=0.02), aged between 44 and 59 (p=0.02) and have a previous history of percutaneous coronary angioplasty (p=0.003). Conclusions/Implications: Despite the fact that the entire study sample were diagnosed with ACS, approximately one in five (20%) perceived that they were less likely than other people of the same age to experience a heart attack in the future. These findings highlight the need for specific and targeted education of both men and women in Ireland with respect to the risks for heart disease and heart attacks.